ALLOPLASTIC RECONSTRUCTION OF THE TEMPOROMANDIBULAR JOINT - Rushil R. DANG; Pushkar MEHRA (Istanbul University, 2017)
Temporomandibular joint reconstruction (TMJR) is often necessary for patients with severe and/or refractory TMJ disease who have failed conservative treatment. TMJR aids to improve masticatory function and is associated with improved quality of life outcomes. Currently, alloplastic reconstruction is considered as the treatment of choice in most severe TMJ disorders due to its many advantages inclusive but not limited to early mobilization, stable longterm results, and significant improvement in jaw function. Broadly speaking, two types of TMJR prostheses are available for reconstruction: 1) stock, and, 2) custommade prostheses. The purpose of this article is to provide the reader with a brief overview of the basic principles and fundamentals of TMJR while referencing pertinent existing literature.